Perbedaan Kemampuan Shooting Sepak Bola Pemain Depan, Tengah dan Belakang SSB Bintang Jaya Kebumen - Mudayat Mudayat; Ibnu Prasetyo Widiyono; Riyan Jaya Sumantri; Puput Widodo; Yogi Ferdy Irawan; Mokhamad Parmadi Mokhamad Parmadi; Ahmad Syarif; Alfiah Rizqi Azizah; Taufik Hidayat (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The aim of this research is to determine the differences in shooting ability between the front, middle and back football players of SSB Bintang Jaya Kebumen. The population in this study were senior SSB Bintang Jaya players aged over 17 years. The instrument used by researchers in collecting data was the shooting test on goal. The data analysis used in this research is the analysis of variance ( anova) test and the Tukey test to find out where the differences are. From these results it can be seen that Fhit > F(v1,v2) namely 482.,5 > 3.34 so Ho is rejected, meaning there is a significant difference between the shooting abilities of the front, middle and back players. As a result of the analysis and testing of the research hypothesis, the conclusion from the calculations that have been carried out is that there is a significant difference between the front, middle and back players in terms of shooting ability, where the front players have better shooting ability than the middle and back players. Keywords: Shooting, Football, Kebumen